Hadroh Nusantara: The Integration of Calligraphy, Geometry, and Esthetic Worship in Sufi Tradition - Intan Umi Khofifah; Irkham Auladi; Supriyanto Supriyanto; Rohmat Ilham Romadhon; Rizki Nur Khanifah (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
This study addresses the limited research that integrates visual, geometric, and spiritual dimensions within the tradition of Hadroh Nusantara. The objective of this research is to analyze how calligraphy, geometry, and the aesthetics of worship form an integrated system within hadroh as a Sufi expression. The study employs a qualitative approach using literature review and symbolic analysis of visual, musical, and performative elements in hadroh practices. The findings reveal that calligraphy functions as both a visual identity and a medium that directs spiritual awareness, while geometry appears in rhythmic patterns and formations that reflect collective order. The aesthetics of worship are manifested through the practice of selawat, dhikr, and embodied etiquette that create a sacred atmosphere. These three elements are not separate, but interrelated within a unified religious aesthetic system that connects artistic expression with spiritual experience. The study concludes that Hadroh Nusantara represents a form of cultural Sufism that integrates visual, auditory, and performative dimensions into a collective spiritual experience, and contributes significantly to cultural da’wah and contemporary Islamic art discourse.